Final answer:
The polynomial equation with zeros at x = -2, x = 0, x = 3, and x = 5 is formed by multiplying the factors associated with each zero, resulting in y = x(x + 2)(x - 3)(x - 5).
Step-by-step explanation:
When finding a polynomial equation based on its zeros, each zero correspond to a factor of the polynomial. Every zero of a polynomial equation represents a point where the graph of the polynomial touches or crosses the x-axis.
The polynomial factors for zeros at x = -2, x = 0, x = 3, and x = 5 would be (x + 2), x, (x - 3), and (x - 5), respectively.
Thus, to get the polynomial equation, we multiply the factors associated with each zero:
y = x(x + 2)(x - 3)(x - 5)
Accordingly, the correct option is:
D) y = x(x + 2)(x - 3)(x - 5)